1996
DOI: 10.1038/ki.1996.268
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of angiotensin II receptor blockade in normotensive subjects

Abstract: Several new non-peptide, orally active, angiotensin II receptor antagonists have recently been developed which enable to block the renin-angiotensin system at the AT1 receptor site. In contrast to angiotensin converting enzyme (ACE) inhibitors, these antagonists do not interfere with the metabolism of kinins. The effect of these agents on renal function may thus potentially differ from those of ACE inhibitors. Therefore, the renal pharmacology of various angiotensin II receptor antagonists has been examined in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(69 citation statements)
references
References 26 publications
3
62
0
4
Order By: Relevance
“…Thiazide diuretics reportedly increase whereas losartan and ACEi lower uric acid levels (41)(42)(43). In our study, uric acid levels were significantly higher among patients who reported use of thiazide diuretics but use did not confound the relationship between uric acid and cC-GFR.…”
Section: Discussionsupporting
confidence: 44%
“…Thiazide diuretics reportedly increase whereas losartan and ACEi lower uric acid levels (41)(42)(43). In our study, uric acid levels were significantly higher among patients who reported use of thiazide diuretics but use did not confound the relationship between uric acid and cC-GFR.…”
Section: Discussionsupporting
confidence: 44%
“…However, losartan's effect could be mediated in part by its known uricosuric action (20), because uric acid levels tended to be lower in the losartan-treated rats. The ability of losartan to lower uric acid is unique to losartan and is not observed in other AT 1 receptor antagonists (3). Further studies will be required to determine whether losartan provides any superior effect over other means for blocking the renin-angiotensin system in hyperuricemic rats.…”
Section: Discussionmentioning
confidence: 99%
“…3A), and both prevented the arteriolopathy (Table 3). Interestingly, uric acid levels tended to be lower in the losartan group compared with untreated controls (P ϭ 0.054, Table 3), which likely relates to the fact that losartan has some uricosuric activity (3,20).…”
mentioning
confidence: 99%
“…Since regression of the myocardial fibrosis was observed only in the losartan-treated group, the anti-fibrotic effect of improving anemia might not be significant over 6 months. A feature of losartan that differentiates it from other AT1-R antagonists is its lowering of serum UA (42), but this effect is due to the ability of the losartan molecule (not its active metabolite) to interfere with urate reabsorption in the renal proximal tubules (43). Thus its effects are closely related to renal function.…”
Section: Discussionmentioning
confidence: 99%